AUDIO BOOKS AS TEACHING MEDIA TO BLIND STUDENTS IN LEARNING EFL - Fansury, Andi Hamzah; Lutfin, Nursamsilis; Arsyad, Susalti Nur (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
The focus of this study on the implementation of audio books as teaching media for blind students in learning English. The purpose of this study was to determine the implementation of audio books as teaching media for blind students in learning English and to find out audio books used in learning EFL. The study was conducted at SLB YAPTI Makassar with a number of samples taken were 20 students conducted randomly. The instruments in this study were tests, observations, and questionnaires. The results of the study show that the implementation of audio books as teaching media for blind students in learning English can help students in the learning process. The implementation of the audio book also increases student motivation in learning because it makes it easier for students to study anywhere and anytime.